Field classification-based novel fuzzing case generation for ICS protocols - Kim, Sung Jin; Shon, Taeshik (Journal of Supercomputing, 2018)
An industrial control system combined with IT is not a special thing; however, cyber security in this field does not mature. Therefore, vulnerability analysis techniques for protocols used in this field are clearly needed. In this paper, we propose a novel test case generation technique for a fuzzing test that can be used for various industrial control system protocols. The proposed fuzzing test is designed for generating a cross-field fuzzing test case because of field dependencies, a characteristic of industrial control system protocols. Additionally, we focus on multilayer testing because the weaknesses of lower layer protocols are inherited by upper layer protocols.
Keywords: Field test; Fuzzing tests; Industrial control systems; Test case generation; Vulnerability analysis; Cross-field test; Fuzzing test; Industrial control system protocol; Test case generation; Vulnerability analysis